Three New Min-Max Variations of the Hardy-Hilbert Integral Inequality (Journal of Informatics and Mathematical Sciences, 2025)
Building on the work of Li and He in 2007, this article presents three new variations of the Hardy-Hilbert integral inequality using minimum and maximum kernel functions. Detailed proofs are provided.